Peran Ultrasonografi dalam Evaluasi Pasca Operasi - Andi Friadi (Andalas Obstetrics And Gynecology Journal, 2020)
The role of ultrasonography (USG) in postoperative gynecology is to assess and evaluate postoperative complications. Ultrasonography are the methods which is noninvasive hence minimize the risk during examination and decrease discomfort the patients. In this literature review, we will explain three main topic role of ultrasound to evaluate postoperative condition such as hematoma, injuries due to the urinary tract and residive mass especially for gynecology oncology cases. Hematoma divided into hematoma on the stump of (the vault is hematoma) and subfascial hematoma. The use of ultrasonography also to evaluate injuries at organ of the urinary tract, especially kidney and ureters. There are two methods which are transabdominally and transvaginally to evaluate the ejection of urine that can confirm that there are no obstruction in the ureter. In addition there is a ultrasound can be used to assess hydronephrosis. In cases of cancer, ultrasound can be used to evaluate residive mass in upper abdomen such as peritoneum (peritoneal carcinomatosis) and liver metastases. Keywords: ultrasonography, hematoma, hydronephrosis, residive mass